An innovative cation regulation-based anaerobic fermentation strategy for enhancing short-chain fatty acids production from waste activated sludge: Metal ion removal coupled with Na+-regulation. (July 2021) - He, Junguo; Pang, Heliang; Pan, Xinlei; Zheng, Yanshi; Wang, Ling; Xu, Jie; Li, Lin; Yan, Zhongsen
Graphical abstract: Highlights: Cation-regulation strategy could remarkably enhance anaerobic fermentation of WAS. Na + -regulation induced secondary hydrolysis of CER-solubilized sludge with EPS disruption. Considerable SCFAs of 439.9 mg COD/g VSS was produced through 4-day fermentation. Remarkable sludge solid reduction of 6.41 g VSS/L (51.6% of VSS) was achievable. More than 77.9% of SCOD was composed of nitrogen-free organic matters. Abstract: This study proposed a cation-regulation strategy based on metal ion removal coupled Na + -regulation for enhancing anaerobic fermentation of waste activated sludge. The optimal treatment condition was: cation-exchange resin dosage of 1.75 g/g SS for 1-day treatment, followed by Na + -enhanced anaerobic fermentation at NaCl concentration of 20 g/L. The CER induced sludge solubilization and the Na + -regulation treatment triggered secondary hydrolysis of CER-solubilized sludge, causing remarkable sludge disintegration and extracellular polymeric substance (EPS) disruption. Numerous SCOD of 6588 mg/L (SCOD/TCOD = 40.6%) was released within 2 days, and the short-chain fatty acids (SCFAs) of 439.9 mg COD/g VSS was produced through 4-day anaerobic fermentation. More than 59% of the SCFAs was composed of acetate and propionate. Nitrogen-free organic matters (i.e. SCFAs and carbohydrates) accounted for 77.9% of SCOD, while considerable sludge solid reduction (51.6% of total VSS) was achievable, which was beneficial for fermentative liquid utilization and sludge disposal.